Krajobrazy przyziemne i usłyszane. Wokół twórczości Forresta Gandera - Pawlus, Tomasz (Przestrzenie Teorii, 2025)
The article explores the relationship between poetry and landscape in the works of Forrest Gander, focusing on his approach to ecopoetics and transdisciplinarity. The author examines how landscape in Gander’s poetry functions as a dynamic, multilayered relational space that incorporates the nat ural, cultural and historical dimensions of perception. The concept of the “listenedto landscape” is highlighted as an object of ethical attention and cognitive practice. The analysis also considers the influence of Martin Heidegger and Maurice Merleau-Ponty on Gander’s way of experiencing and representing landscape in his poetry. The text emphasizes the palimpsestic and polyphonic nature of his works, situating them within contemporary reflections on the ecological crisis and new epis temological strategies in literature.